Simulated performances of pixelated CsI(Tl) scintillation screens with different micro-column shapes and array structures in X-ray imaging - Chen, Hui (Sci Rep, 2018)
The performances of the pixelated CsI(Tl) scintillation screens based on oxidized silicon micro-pore array templates with different CsI(Tl) micro-column shapes and array structures in X-ray imaging were simulated using the Geant4 Monte Carlo simulation code. The shapes of the micro-columns include square, hexagonal and circular, and the array structures include square and hexagonal arrangements. The pitch size of the pixelated CsI(Tl) scintillation screens was set to 4 µm, and the incident X-ray energy was set to 20 keV. The ratios of the number of scintillation photons that propagate along the CsI(Tl) micro-columns to the total number of scintillation photons of the micro-columns gradually decrease with the increase in total reflection time on the lateral surfaces of the micro-columns. However, these ratios are closely related to the shapes of the micro-columns and the incident positions of X-ray on the cross-sections of the micro-columns, especially for the circular micro-column. The sequence of bottom light outputs stimulated by a uniform flood field of X-ray from high to low corresponds to the circular, square and hexagonal CsI(Tl) micro-columns with the same cross-section areas. In addition, all spatial resolutions in terms of modulation transfer functions (MTFs) for the pixelated CsI(Tl) scintillation screens with square and hexagonal array structures are over 100 lp/mm. However, the resolution for the pixelated screen with the hexagonal array structure is approximately 8.5% higher than that for the screen with the square array structure. Moreover, the former screen has a higher detective quantum efficiency (DQE) than the latter screen at the same thickness. The pixelated CsI(Tl) scintillation screen with circular micro-column and hexagonal array structure in X-ray imaging has superior performance compared to other pixelated screens in this work.